Prostaglandin-dependent modulation of dopaminergic neurotransmission elicits inflammation-induced aversion in mice - Fritz, Michael; Klawonn, Anna M.; Nilsson, Anna; Singh, Anand Kumar; Zajdel, Joanna; Björk Wilhelms, Daniel; Lazarus, Michael; Löfberg, Andreas; Jaarola, Maarit; Örtegren Kugelberg, Unn; Billiar, Timothy R.; Hackam, David J.; et al. (The Journal of clinical investigation, 2016)
Systemic inflammation causes malaise and general feelings of discomfort. This fundamental aspect of the sickness response reduces the quality of life for people suffering from chronic inflammatory diseases and is a nuisance during mild infections like common colds or the flu. To investigate how inflammation is perceived as unpleasant and causes negative affect, we used a behavioral test in which mice avoid an environment that they have learned to associate with inflammation-induced discomfort. Using a combination of cell-type–specific gene deletions, pharmacology, and chemogenetics, we found that systemic inflammation triggered aversion through MyD88-dependent activation of the brain endothelium followed by COX1-mediated cerebral prostaglandin E2 (PGE2) synthesis. Further, we showed that inflammation-induced PGE2 targeted EP1 receptors on striatal dopamine D1 receptor–expressing neurons and that this signaling sequence induced aversion through GABA-mediated inhibition of dopaminergic cells. Finally, we demonstrated that inflammation-induced aversion was not an indirect consequence of fever or anorexia but that it constituted an independent inflammatory symptom triggered by a unique molecular mechanism. Collectively, these findings demonstrate that PGE2-mediated modulation of the dopaminergic motivational circuitry is a key mechanism underlying the negative affect induced by inflammation.